Anti‐mouse CD52 monoclonal antibody ameliorates intestinal epithelial barrier function in interleukin‐10 knockout mice with spontaneous chronic colitis. Issue 2 (February 2015) - Wang, Honggang; Dong, Jianning; Shi, Peiliang; Liu, Jianhui; Zuo, Lugen; Li, Yi; Gong, Jianfeng; Gu, Lili; Zhao, Jie; Zhang, Liang; Zhang, Wei; Zhu, Weiming; et al.
Summary Intestinal inflammation causes tight junction changes and death of epithelial cells, and plays an important role in the development of Crohn's disease (CD). CD52 monoclonal antibody (CD52 mAb) directly targets the cell surface CD52 and is effective in depleting mature lymphocytes by cytolytic effects in vivo, leading to long‐lasting changes in adaptive immunity. The aim of this study was to investigate the therapeutic effect of CD52 mAb on epithelial barrier function in animal models of IBD. Interleukin‐10 knockout mice (IL‐10−/−) of 16 weeks with established colitis were treated with CD52 mAb once a week for 2 weeks. Severity of colitis, CD4+ lymphocytes and cytokines in the lamina propria, epithelial expression of tight junction proteins, morphology of tight junctions, tumour necrosis factor‐α (TNF‐α)/TNF receptor 2 (TNFR2) mRNA expression, myosin light chain kinase (MLCK) expression and activity, as well as epithelial apoptosis in proximal colon were measured at the end of the experiment. CD52 mAb treatment effectively attenuated colitis associated with decreased lamina propria CD4+ lymphocytes and interferon‐γ/IL‐17 responses in colonic mucosa in IL‐10−/− mice. After CD52 mAb treatment, attenuation of colonic permeability, increased epithelial expression and correct localization of tight junction proteins (occludin and zona occludens protein‐1), as well as ameliorated tight junction morphology were observed in IL‐10−/− mice. CD52 mAb treatment also effectively suppressed the epithelial apoptosis, mucosa TNF‐α mRNA expression, epithelial expression of long MLCK, TNFR2 and phosphorylation of MLC. Our results indicated that anti‐CD52 therapy may inhibit TNF‐α/TNFR2‐mediated epithelial apoptosis and MLCK‐dependent tight junction permeability by depleting activated T cells in the gut mucosa.